Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
[tex] x^{3} + x [/tex]
x= -3
Plug the value of x into the equation. x = -3
After putting the value of x in it now looks like:
[tex] -3^{3} + (-3) [/tex]
Now solve:
[tex] -3^{3} [/tex] is the same as: (-3) x (-3) x (-3)
(-3) x (-3) x (-3) = -27
Finish the equation by adding -3 to -27 (same thing as subtracting 3 from -27)
-27 + (-3) = -30
x = -30
x= -3
Plug the value of x into the equation. x = -3
After putting the value of x in it now looks like:
[tex] -3^{3} + (-3) [/tex]
Now solve:
[tex] -3^{3} [/tex] is the same as: (-3) x (-3) x (-3)
(-3) x (-3) x (-3) = -27
Finish the equation by adding -3 to -27 (same thing as subtracting 3 from -27)
-27 + (-3) = -30
x = -30
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.